Synthesis, molecular docking, molecular dynamics and evaluation of Drug-Likeness properties of the fused N-Formyl pyrazoline substituted new dehydroepiandrosterone derivatives - Capan, Irfan; Shehu, Abdulmalik; Sert, Yusuf; Celik, Ismail; Erol, Meryem; Koca, Irfan; Servi, Suleyman (Taylor & Francis Inc, 2023)
The hybrid molecules bearing heterocyclic structures in the A or D rings of steroids have significant biological activity. 16 (E)-Hetereoarylidene steroids were synthesized from the reaction of different heteroaromatic carbaldehydes and trans-Dehydroepiandrosterone (DHEA) in a basic medium. Then, synthesis of the N-formyl pyrazoline substituted new DHEA derivatives were carried out from the reaction of hydrazine hydrate and 16 (E)-hetereoarylidene steroids. The structures of the synthesized compounds were elucidated by elemental analysis, FT-IR, H-1 NMR, and C-13 NMR spectroscopy. To investigate the activation pathway of synthesized N-formyl pyrazoline substituted steroid derivatives, a molecular docking study was performed on human cytochrome P450-(CYP17A1: PDB ID 5IRQ) with the help of the free AutoDock Vina. 100 ns molecular dynamic simulation process was performed to monitor the behavior of the complex structure formed by CYP17A1 and to calculate the stability over time of 2a and 2d (-9.8 kcal/mol), which gave the lowest value according to the results obtained in the molecular docking study with AutoDock Vina. Accordingly, RMSD, RMSF, Rg, and SASA analyzes of 2a and 2d were performed, and MMPBSA was calculated. Lastly, the ADMET (absorption, distribution, metabolism, excretion, and toxicity) analyses of the novel steroid derivatives were investigated. Communicated by Ramaswamy H. Sarma
Keywords: trans-Dehydroepiandrosterone; steroid; pyrazoline; molecular docking; molecular dynamic; ADMET analysis